Unveiling the Challenges Faced By Malaysian Housing Developers through Government Policy Changes - Nuruddin, Azlan Raofuddin; Bakar , Syed Putra Syed Abu; Jaafar , Mastura (Penerbit Universiti Sains Malaysia, 2015)
Despite being receptive to new ideas, Malaysian housing developers must be responsive to the demands imposed upon the industry. One of the external factors that influence the growth of housing development firms is the intervention of government. The role of government in shaping the housing industry is especially pertinent because most land matters involve dealing directly with local and state authorities. The regulations imposed by the government are perceived as imbalanced and serve only to increase the challenges confronted by housing developers to maintain their survivability. This paper is therefore aimed at disclosing the related challenges faced by housing developers with respect to current government issues. Appropriately, 10 Malaysian housing developers were interviewed to determine the reasons for their success in achieving business sustainability, including eliciting responses for the myriad of challenges faced. To analyse the findings, a qualitative approach was used that is based on the content analysis method. All the interviewees highlighted several challenges that have impeded their progress in the management of the housing development business. Interestingly, the most notable challenge revealed by the respondents is related to the vagaries of the government rules and processes. Among the grievances mentioned by the participants were late approvals, sudden changes of rules, non-uniform compliances and other similar issues. Hence, there is a serious need for housing developers and the government to work in tandem, not only to minimise complaints directed towards the government but also to concertedly embrace changes in terms of policies and laws. A mutually beneficial wave of innovation is thus advocated, where the vested interests of both housing developers and house buyers will be protected accordingly. In addition, with good comprehension of the government procedures, the creation of economic empowerment and development will be easily realised